Analysis Of Product Damage Levels For Smooth Production In Mr. Eko’s Oncom Business In Raman Aji Village Lampung Timur - Ndaruwati, Mega Putri; Febriyanto, Febriyanto (Universitas Muhammadiyah Metro, 2023)
Analysis Of Product Damage Levels For Smooth Production In Mr. Eko’s Oncom Business In Raman Aji Village Lampung Timur This study aims to determine whether the level of product damage as a whole is still within the tolerable limit, the type of product damage and what percentage, and what factors affect product damage during 2020 at Mr Eko's Oncom Business in Raman Aji Village, East Lampung. The type of research used is quantitative research. This study uses the Statistical Quality Control (SQC) method with the tools of (1) Control Chart, (2) Pareto, (3) Fishbone. The results of this study are the overall level of product damage that occurred during 2020 at Mr Eko's Oncom Business in Raman Aji Village, East Lampung is still within tolerable limits with an average product damage value of 4.54%, UCL of 8.25%, and LCL by 0.84%. The types of product damage were color (mushrooms were not perfectly evenly distributed) with a percentage of 62%, shape and size with a percentage of 25%, and too soft texture with a percentage of 13%. The factors that affect the damage to oncom products are workers who are less thorough and less trained, raw materials that are not good in checking, equipment that is no longer standard to use and lack of maintenance, unsanitary environmental conditions and the presence of smoke resulting from combustion and oncom printing and production methods are still carried out by human labor.